Pengaruh Latihan Triangle Terhadap Hasil Passing Futsal Peserta Ekstrakurikuler SDN Mustikasari III Kota Bekasi - Darmawan, Rendy; Ningrum, Desy Tya Maya; Denatara, Eskar Tri; ‘Ala, Faridatul; Pasaribu, Ahmad Muchlisin Natas (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Futsal has a significant impact on students, including elementary school students, as evidenced by the increasing number of futsal field facilities and the proliferation of elementary school and inter-club championships in various regions. The objectives of this study are as follows: First, to determine the impact of the Triangle Training Method on passing techniques among extracurricular participants at SDN Mustikasari III. Second, to assess improvements in passing skills among extracurricular participants at SDN Mustikasari III using the Triangle Training Method. Third, to determine the results of passing techniques among extracurricular participants at SDN Mustikasari III. The method used in this study is a quantitative method to systematically, objectively, and testably examine cause-and-effect relationships and research variables, utilizing measurements, observations, and theory testing. The research design selected was a Pre-Experimental Design with a One Group Pretest-Posttest Design model. The results of this study indicate that the Triangle training method is effective in improving the basic passing technique of futsal extracurricular participants at SDN Mustikasari III in Bekasi City.